Pre-Service Teacher Perceptions of School Counsellor Responsibilites - Joy, Rhonda M.; Hesson, Jackie; Harris, Gregory (Canadian Journal of Counselling and Psychotherapy, 2011)
Teachers have tremendous impact on school counselling service utilization in terms of teacher-counsellor consultation and student referral. Thus, ensuring that teachers understand the roles and responsibilities of school counsellors is critical. As teachers’ understanding of the school counselling role can be impacted during preservice teacher training and little has been published on preservice teachers’ views of school counselling, the authors of the current study opted to explore preservice teachers’ perceptions of school counsellor responsibilities. Ninety preservice teachers from Newfoundland and Labrador completed the survey. Results suggested that although preservice teachers appear to have a moderate degree of knowledge regarding a subset of school counsellor responsibilities, more effort is needed to systematically inform preservice teachers about the responsibilities of the school counsellor role. Implications for training and for school counsellor practice are discussed.